The Impact of Digitalisation and Information Technology on the Audit Process and Auditor Decision-Making - Sri Nurul Izzah; Nur Huzaemah; Amiruddin Amiruddin (Yayasan Riset dan Pengembangan Intelektual, 2025)
Developments in digitalisation and information technology have changed the perspective on the auditing profession, shifting from traditional manual practices to integrated technology in auditing. The purpose of this study is to analyse in depth how technologies such as Artificial Intelligence (AI), Big Data Analysis, Blockchain, Robotic Process Automation (RPA), and Enterprise Resource Planning (ERP) influence audit procedures and decision-making by auditors. Using a descriptive and exploratory literature review approach, this study combines the latest empirical and conceptual findings for the period 2021 to 2025. The results show that digitalisation improves efficiency, accuracy, and transparency in auditing through process automation and large-scale data analysis. The use of AI and RPA allows auditors to focus more on strategic analysis and risk assessment, while blockchain improves the reliability of audit evidence by recording immutable transactions. However, this transformation also brings challenges such as a lack of digital competence among auditors, the risk of dependence on automated systems, and ethical and cybersecurity issues. Therefore, success in digital auditing depends not only on the use of technology, but also on good digital literacy, ready infrastructure, and effective ethical governance. This study contributes theoretically to the understanding of the relationship between digitisation and auditor decision-making, and points the way for future research on the impact of technology on auditor independence and professionalism in the digital age.